Incident comorbidities in patients with chronic hypoparathyroidism after thyroidectomy: a multicenter nationwide study - Díez, Juan J.; Anda, Emma; Pérez-Corral, Begoña; Paja, Miguel; Alcázar, Victoria; Sánchez-Ragnarsson, Cecilia; Orois, Aida; Romero-Lluch, Ana R.; Sambo, Marcel; Oleaga, Amelia; Caballero, Águeda; Alhambra, María R.; et al. (Frontiers in Endocrinology, 2024)
Purpose. Population-based and registry studies have shown that chronic hypoparathyroidism is accompanied by long-term complications. We aimed to evaluate the risk of incident comorbidity among patients with chronic postsurgical hypoparathyroidism in real-life clinical practice in Spain.Methods. We performed a multicenter, retrospective cohort study including patients with chronic postsurgical hypoparathyroidism lasting ≥3 years with at least a follow-up visit between January 1, 2022 and September 15, 2023 (group H). The prevalence and incidence of chronic complications including chronic kidney disease, nephrolithiasis/nephrocalcinosis, hypertension, dyslipidemia, diabetes, cardiovascular disease, central nervous system disease, mental health disorders, eye disorders, bone mineral density alterations, fracture and cancer were evaluated. Patient data were compared with a group of patients who did not develop hypoparathyroidism, matched by gender, age, and follow-up time after thyroidectomy (group NH).Results. We included 337 patients in group H (median [IQR] age, 45 years; median time of follow-up, 8.9 [6.0-13.0] years; women, 84.3%) and 669 in group NH (median age, 47 [37-55] years; median time of follow-up, 8.0 [5.3-12.0] years; women, 84.9%). No significant differences were found in the prevalence of comorbidities at the time of thyroidectomy between both groups. In multivariable adjusted analysis, patients with chronic hypoparathyroidism had significantly higher risk of incident chronic kidney disease (OR, 3.45; 95% CI, 1.72-6.91; P<0.001), nephrolithiasis (OR, 3.34; 95% CI, 1.55-7.22; P=0.002), and cardiovascular disease (OR, 2.03; 95% CI, 1.14-3.60; P=0.016), compared with patients without hypoparathyroidism. On the contrary, the risk of fracture was decreased in patients with hypoparathyroidism (OR, 0.09; 95% CI, 0.01-0.70; P=0.021).This study demonstrates that, in the clinical practice of Spanish endocrinologists, a significant increase in the risk of chronic kidney disease, nephrolithiasis and cardiovascular disease, as well as a reduction in the risk of fractures is detected. These results are of interest for the development of new clinical guidelines and monitoring protocols for patients with hypoparathyroidism.